2017
DOI: 10.1038/srep43153
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy down regulates pro-inflammatory mediators in BV2 microglial cells and rescues both LPS and alpha-synuclein induced neuronal cell death

Abstract: Autophagy is a fundamental cellular homeostatic mechanism, whereby cells autodigest parts of their cytoplasm for removal or turnover. Neurodegenerative disorders are associated with autophagy dysregulation, and drugs modulating autophagy have been successful in several animal models. Microglial cells are phagocytes in the central nervous system (CNS) that become activated in pathological conditions and determine the fate of other neural cells. Here, we studied the effects of autophagy on the production of pro-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
64
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(75 citation statements)
references
References 50 publications
7
64
1
Order By: Relevance
“…Note that in some culture settings, toxic effects of aggregated forms of αS have been reported at much lower concentrations (Kim et al, 2013;Zhang et al, 2005). Concentrations comparable to those used by us in the present study were, however, required in other paradigms (Bussi et al, 2017;Hoffmann et al, 2016). We have no definite explanation for such differences, which may be attributable to different culture conditions and various procedures used to generate aggregated species of αS.…”
Section: Aggregated But Not Monomeric Forms Of αS Stimulate Glutamamentioning
confidence: 48%
See 1 more Smart Citation
“…Note that in some culture settings, toxic effects of aggregated forms of αS have been reported at much lower concentrations (Kim et al, 2013;Zhang et al, 2005). Concentrations comparable to those used by us in the present study were, however, required in other paradigms (Bussi et al, 2017;Hoffmann et al, 2016). We have no definite explanation for such differences, which may be attributable to different culture conditions and various procedures used to generate aggregated species of αS.…”
Section: Aggregated But Not Monomeric Forms Of αS Stimulate Glutamamentioning
confidence: 48%
“…Using a model system of purified microglial cell cultures, we established that amyloid fibrils of αS had the capacity to stimulate FIGURE 5 Dopamine prevents glutamate release induced by αSa in microglial cells through D 1 receptor activation. Concentrations comparable to those used by us in the present study were, however, required in other paradigms (Bussi et al, 2017;Hoffmann et al, 2016). Data are means ± SEM (n = 6).…”
Section: Aggregated But Not Monomeric Forms Of αS Stimulate Glutamamentioning
confidence: 54%
“…The inflammatory and neurotoxic mediator NO is released from activated microglia. Excessive release of NO may be involved in contribute to the development of neurodegenerative diseases . NO is synthesized from l ‐arginine by iNOS in microglia .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the disruption of the integrity of the blood-brain barrier and also endothelial cell "cluster" formation, which occur in MPTP-intoxicated mice, were diminished by trehalose through its ability to restore the levels of two tight junctional proteins (ZO-1 and occludin). In a recent study, Bussi et al (2017) showed that exposure to both rapamycin and trehalose efficiently promoted autophagy and decreased the release of proinflammatory mediators, including NO, in response to LPS and αsynuclein in BV2 microglial cells (Table 1). The link between (Table 1; He et al, 2014).…”
Section: Anti-inflammatory Effect Of Trehalosementioning
confidence: 99%
“…Moreover, trehalose efficiently attenuated NF-κB activation by down-regulation of toll-like receptor 4 (TLR4) and protected the PD animal model from LPS-mediated neuroinflammation (Minutoli et al, 2008). In a recent study, Bussi et al (2017) showed that exposure to both rapamycin and trehalose efficiently promoted autophagy and decreased the release of proinflammatory mediators, including NO, in response to LPS and αsynuclein in BV2 microglial cells (Table 1). Autophagy may play a critical role in the control of inflammatory responses through inhibition of spurious inflammasome activation and down-regulation of immune response, induced by the activated inflammasome (Lupfer et al, 2013;Nakahira et al, 2011;Saitoh et al, 2008), and inhibition of type I interferon responses either directly or indirectly (Konno, Konno, & Barber, 2013;Liang et al, 2014;Saitoh et al, 2009).…”
Section: Anti-inflammatory Effect Of Trehalosementioning
confidence: 99%